Asimilasi Budaya Dalam Pernikahan Antara Suku Banjar Dan Suku Dayak - Wahyu Fitrianoor (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2021)
The sense of tribal fanaticism that is still thick in society makes a reference in marriage because according to them, ethnic background is related to one's religious characteristics and understanding. Migration flows for economic activities brought the Banjarese to the city of Palangkaraya, which eventually mingled with the Dayak tribes in the area. Marriages between these two tribes also occur a lot, be it because of economic, social, and theological factors. Each of these two tribes contrasts sharply in marriage culture. This difference can be seen from the strong influence of Islam on Banjar culture and Dayak culture which is still thick with Kaharingan teachings.This study aims to examine the cultural assimilation between the Banjar and Dayak tribes that have occurred in the city of Palangkaraya, and its implications for the lives of the Banjar and Dayak couples in married life with the research focus covering: (1) how the cultural assimilation of the Banjar and Dayak people in the city Palangkaraya Islamic law perspective and positive law. (2) how is the cultural assimilation of the Banjar and Dayak tribes in Palangkaraya from the perspective of social exchange theory, (3) what are the implications of the cultural assimilation of the Banjar and Dayak tribes in domestic life from the perspective of legal compliance theory.This research is classified as field research, with a sociological-empirical approach. Data were collected using in-depth interviews, documentation, and observation techniques. Technical data analysis with data collection, data reduction, synthesis, and data verification. Research information was obtained from religious leaders, traditional leaders, academics, cultural observers, cultural practitioners, and couples from the Banjar tribe with the Dayak tribe.There are three findings in this study. First, the cultural assimilation of the Banjar and Dayak people in Palangkaraya City from the perspective of Islamic law and positive law, not all of the culture is in line with Islam, but Islam acts as a filter for anything that deviates from its teachings so that it has a positive impact on awareness. To positive law, these two assimilations in the perspective of social exchange theory are a mix that has long existed, due to economic, social, religious, philosophical, and marriage relations themselves, with a balance of costs, rewards, and profits that make this assimilation continue to be harmonious. . Based on this study, the mutualism symbiosis created was due to good economic relations, mutual respect for both customary values and norms with a high tolerance attitude, even though they felt that there was a shift in ancestral values due to friction with the new culture. These three implications of cultural assimilation from the perspective of legal compliance theory, state that the legal compliance of this inter-ethnic couple is at the identification level because they are not maximal in carrying out what is not their custom, this is due to contradictory family doctrines, but there is still solidarity between them. they are even in the midst of these differences.Keywords: Banjar Tribe, Dayak Tribe, Customs in Marriage.